Estimasi Persentase Karbon Organik pada Tanah di Hutan Mangrove Alami, Perancak, Jembrana, Bali - IGA Ayu Mirah Indraiswari; I Dewa Nyoman Nurweda Putra (Journal of Marine Research and Technology, 2018)
Mangrove is one of the coastal ecosystems that play a role in taking and storing a number of carbon known as Coastal Blue Carbon. Soil storage (below-ground) in mangrove forests has a potential potential of 50% to 90% more than the total carbon stock of the ecosystem. This study was conducted at 3 stations in Perancak Mangrove Forest, Jembrana, Bali with the aim of estimating the percentage of organic carbon and knowing the vertical variation percentage of organic carbon in the soil. Sampling time was conducted in June 2015. The data required to calculate the percentage of organic carbon in the soil is the depth of soil samples, depth and sub-sample intervals, and bulk density. From the results of the study found that the percentage of organic carbon in the soil in the natural mangrove forest Perancak by 50.235% or 185.968 Mg / ha. Vertically the percentage of organic carbon in soils in natural mangrove forests Perancak varies. The lowest bulk density value at depth (0-15 cm) of 0.07 g / cm3 at station 1 and highest at depth (> 100 cm) of 0.20 g / cm 3 at station 3; value of the lowest organic carbon% at depth (> 100 cm) of 47.899% at station 2 and highest at depth (50-100 cm) of 51.821% at station 1; the lowest soil C value at depth (0-15 cm) is 17,361 Mg ha-1 and the highest at depth (50-100 cm) is 62,962 Mg ha-1 at station 1.